2021
DOI: 10.1002/aic.17250
|View full text |Cite
|
Sign up to set email alerts
|

A virucidal face mask based on the reverse‐flow reactor concept for thermal inactivation of SARS‐CoV‐2

Abstract: While facial coverings reduce the spread of SARS-CoV-2 by viral filtration, masks capable of viral inactivation by heating can provide a complementary method to limit transmission. Inspired by reverse-flow chemical reactors, we introduce a new virucidal face mask concept driven by the oscillatory flow of human breath. The governing heat and mass transport equations are solved to evaluate virus and CO 2 transport. Given limits imposed by the kinetics of SARS-CoV-2 thermal inactivation, human breath, safety, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…It has been proposed that purposefully engineered materials with nanostructured surfaces can eliminate enveloped viruses such as SARS-CoV-2 i.a., on masks and be self-disinfectant ( 85 ). Other ways in which materials technology can improve masks is exemplified by a mask under development that lets some SARS-CoV-2 penetrate the mask, but heat-inactivates it ( 86 ). Guha et al suggest that electret materials (i.e., those with a permanent electric charge) may be advantageous for masks ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that purposefully engineered materials with nanostructured surfaces can eliminate enveloped viruses such as SARS-CoV-2 i.a., on masks and be self-disinfectant ( 85 ). Other ways in which materials technology can improve masks is exemplified by a mask under development that lets some SARS-CoV-2 penetrate the mask, but heat-inactivates it ( 86 ). Guha et al suggest that electret materials (i.e., those with a permanent electric charge) may be advantageous for masks ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study showed that commercially available powered air purifying respirator that enhance breathability could prevent headache related to PPE [31] induced by hemodynamic alterations [32] . We are confident that our device will support the rapidly advancing research on filter materials [ 33 , 34 ] and designs [ 35 , 36 ] will lead to engineering of ergonomic masks that do not compromise on filter performance and breathability.…”
Section: Discussionmentioning
confidence: 99%
“…For similar aim, scientists from Massachusetts Institute of Technology (MIT) incorporated a copper mesh into the mask. By applying an electrical current through the mesh, large amounts of ohmic heat are generated, which greatly raise the local temperature and the microbes are killed [ 97 ] . Another approach to kill the aerosol pathogens adhered on the mask relies on the radical species produced by high electric field ( Fig.…”
Section: Functional Designs Of Masks In Pandemic Periodmentioning
confidence: 99%